Multi-Link Operation in IEEE802.11be Extremely High Throughput: A Survey - Abdalhafid, Alsadg A.; Subramaniam, Shamala K.; Zukarnain, Zuriati A.; Ayob, Fahrul H. (Institute of Electrical and Electronics Engineers Inc., 2024)
The evolution of wireless communication has led to the introduction of IEEE 802.11be, a leading-edge wireless standard also referred to as Extremely High Throughput (EHT) or Wi-Fi 7. Multi-Link Operation (MLO) is the most innovative and disruptive technology proposed in this amendment, which holds the potential to revolutionize wireless networks. MLO aims to increase throughput through link aggregation, enhance reliability through redundant frame transmission over multiple links, and decrease latency by utilizing the earliest available link. However, to the best of our knowledge, there is no specific survey or review paper is dedicated solely to MLO, despite the extensive research conducted on Wi-Fi 7. Thus, this survey paper will bridge the gap by presenting an exhaustive overview of cutting-edge research spanning from 2010 to 2023, exclusively focused on MLO characteristics, current status and future directions. This study has discovered several open issues, including backoff count overflow, channel selection, load balancing and channel access fairness. These findings lay the groundwork for future research that has the potential to impact the current status of wireless communication significantly.